2011
DOI: 10.1002/app.34172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on the physicomechanical and thermal properties of high‐density polyethylene/olive husk flour composites

Abstract: In this study, a particular interest was focused on the recovery of lignocellulosic waste of olive husk flour (OHF) by its incorporation as filler in manufacturing composite materials based on high-density polyethylene (HDPE) matrix with various filler contents (10, 20, and 30 wt %). The problem of incompatibility between the hydrophilic filler and the hydrophobic matrix was treated with two methods: the first method consists of using maleic anhydride-grafted polyethylene (MAPE) as compatibilizer in HDPE/OHF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
(17 reference statements)
1
16
0
2
Order By: Relevance
“…The solid waste can be burned to produce electric energy or heat, or turned into activated carbon after a thermal treatment for the removal of poisonous metals from water . The possible use of the solid by‐products as a source of compost material has also been approached . The conversion of olive stone flour (OSF) into viscous polyols, likely to be used in polyurethane foams, was successfully accomplished by total and partial oxypropylation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid waste can be burned to produce electric energy or heat, or turned into activated carbon after a thermal treatment for the removal of poisonous metals from water . The possible use of the solid by‐products as a source of compost material has also been approached . The conversion of olive stone flour (OSF) into viscous polyols, likely to be used in polyurethane foams, was successfully accomplished by total and partial oxypropylation .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable amount of solid waste generated by olive oil extraction, to the best of our knowledge, only a few research works reported in the literature have tackled the use of olive stones as fillers in polymer‐based composite materials. Using the search term “olive stone,” “olive kernel,” or “olive pit” and composites, only eight English scientific publications have been reported by ISI since 1993, six of which were devoted to thermoplastic matrix . Among these reported research works, only two were concerned with polyvinyl chloride (PVC) as a polymer matrix .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b) owing to the presence of hydroxyl groups. The presence of RH aggregates provides an evidence of low compatibility and poor dispersion (Ihamouchen et al 2012). This agglomeration decreases homogeneity of the film and, in consequence, its performance properties.…”
Section: Morphological Analysismentioning
confidence: 97%
“…Among others, their renewability, abundance, lower cost, environmental friendliness and relative non-abrasiveness for the processing machinery have made natural fibres an attractive candidate for reinforcement of polymers (Ahmad Thirmizir et al 2013;Ismail et al 2013). These biocomposites are being used in large number of applications, including but not limited to automotive, building and furniture industries (Butylina et al 2013;Ihamouchen et al 2012). However, their strong hydrophilic behaviour made using natural fibre-reinforced composites is less attractive.…”
Section: Introductionmentioning
confidence: 99%